Impact of Semaglutide on Body Composition and Muscle Mass Maintenance in Patients Undergoing Semaglutide Induced Weight Loss Therapy: A Systematic Review - Zieliński, Daniel; Sędek, Małgorzata; Tambor, Joanna; Pudzisz, Patrycja; Kobylińska, Julia; Krzysiak, Katarzyna (Quality in Sport, 2026)
Background: Semaglutide, a glucagon-like peptide-1 receptor agonist (GLP-1 RA), has emerged as an effective pharmacological therapy for obesity and type 2 diabetes mellitus due to its potent effects on weight reduction and metabolic regulation. However, increasing concerns have arisen regarding its influence on body composition, particularly the preservation of skeletal muscle mass during rapid weight loss. Aim: This systematic review evaluates the impact of semaglutide and related GLP-1-based therapies on body composition, skeletal muscle preservation, metabolic remodeling, and associated risks of sarcopenia during weight reduction therapy. Materials and methods: A systematic analysis of clinical, translational, and mechanistic studies was conducted, focusing on semaglutide-induced changes in fat mass, lean body mass, skeletal muscle function, and molecular pathways associated with muscle metabolism. Results: Semaglutide consistently promotes substantial fat mass reduction with proportionally smaller decreases in lean mass, generally preserving muscle functionality and improving body composition quality. Mechanistic studies suggest additional protective roles through modulation of SIRT1, mitochondrial efficiency, inflammatory suppression, and anabolic signaling. Nevertheless, specific populations, particularly older adults, may remain vulnerable to sarcopenic complications without appropriate nutritional and exercise interventions. Conclusions: Semaglutide represents a highly effective therapy for obesity with generally favorable effects on body composition. Optimal therapeutic outcomes require integrated resistance training, nutritional support, and individualized monitoring to maximize fat loss while preserving skeletal muscle integrity.